Beyond The Wi-Fi Era - Amin, Osama; Dang, Shuping; Abdelhady, Amr M.; Ma, Guoqing; Ye, Jia; Alouini, Mohamed-Slim; Shihada, Basem (Frontiers in Communications and Networks, 2024)
The continual progress pace of the development of the Wi-Fi generations may not fulfill the expected tremendous data growth of future smart-home network devices and applications.Throughout this article, we show a comprehensive design of the futuristic smart-home network that distributes massive data for indoor devices while fully supporting intelligent functions. We start by drawing a vision for various application scenarios of information and communication technologies in smart-home networks beyond the 2030s. Then, we appraise the technical specifications of the candidate intelligent home network. To achieve these technological speculations, we propose a novel holistic networking solution that is efficient and intelligent from service and operation perspectives. Specifically, we detail the proposed network architecture, elements, and enabling technologies. To accelerate the research progress and implementation, we further point out the future research directions. Finally, we discuss the non-technological factors that could affect the future deployment of the proposed network solution.